A novel linear plasmid mediates flagellar variation in Salmonella Typhi. - Baker, S; Hardy, J; Sanderson, K; Quail, M; Goodhead, I; Kingsley, R; Parkhill, J; Stocker, B; Dougan, G (Public Library of Science, 2007)
Unlike the majority of Salmonella enterica serovars, Salmonella Typhi (S. Typhi), the etiological agent of human typhoid, is monophasic. S. Typhi normally harbours only the phase 1 flagellin gene (fliC), which encodes the H:d antigen. However, some S. Typhi strains found in Indonesia express an additional flagellin antigen termed H:z66. Molecular analysis of H:z66+ S. Typhi revealed that the H:z66 flagellin structural gene (fljB(z66)) is encoded on a linear plasmid that we have named pBSSB1. The DNA sequence of pBSSB1 was determined to be just over 27 kbp, and was predicted to encode 33 coding sequences. To our knowledge, pBSSB1 is the first non-bacteriophage-related linear plasmid to be described in the Enterobacteriaceae.